Yield and yield components of rapeseed as influenced by nitrogen and sulphur fertilization (Journal of Oilseed Brassica, 2026)
Effect of nitrogen (N) and sulphur (S) on yield and yield components of rapeseed (BARI Sarisha-14) was studied at Shere-Bangla Agricultural University Farm, Dhaka, Bangladesh during two consecutive Rabi seasons of 2014-15 and 2015-16. The experiment was laid out in split-plot design with three replications, consisted four levels of nitrogen viz., 0 (control), 60, 120, 180 kg ha-1; and four levels of sulphur i.e., 0 (control), 15, 30, 45 kg ha-1. Levels of N and S showed significant effect on yield and yield contributing characters of BARI Sarisha-14. Results showed that application of 120 kg N ha-1 with 45 kg S ha-1 gave the maximum yield. Results also revealed that the highest plant height, number of branches plant-1, number of siliquae plant-1, siliqua length, number of seeds siliqua-1, 1000-seed weight, seed yield, stover yield, biological yield and harvest index were obtained from the combination of 120 kg N with 45 kg S ha-1.